2018
DOI: 10.1017/s1041610217003039
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on wisdom at the end of life: qualitative study of hospice patients aged 58–97 years

Abstract: Objective: Wisdom is a complex trait, and previous research has identified several components of wisdom. This study explored the possible impact of a diagnosis of a terminal illness on the conceptualization and evolution of wisdom while facing the end of life.Design and Participants: Semi-structured qualitative interviews were conducted with 21 hospice patients aged 58-97 years who were in the last six months of their life. Methods:Hospice patients were asked to describe the core characteristics of wisdom, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This is consistent with the role of self-reflection as an essential component of wisdom, as mentioned earlier. A recent study involving qualitative interviews of older adults in hospice care illustrated how the diagnosis of a terminal illness led to greater self-reflection, emotional regulation, and pro-social behaviors (Montross-Thomas et al 2018).…”
Section: Wisdom and Adversity: The Tragedy And Opportunity Of Traumamentioning
confidence: 99%
“…This is consistent with the role of self-reflection as an essential component of wisdom, as mentioned earlier. A recent study involving qualitative interviews of older adults in hospice care illustrated how the diagnosis of a terminal illness led to greater self-reflection, emotional regulation, and pro-social behaviors (Montross-Thomas et al 2018).…”
Section: Wisdom and Adversity: The Tragedy And Opportunity Of Traumamentioning
confidence: 99%
“…The current issue contains three data-based research articles (Bailly et al, 2018;Ihle et al, 2018;Montross-Thomas et al, 2018) from France, USA, and Switzerland, respectively. These papers report stability of spirituality in older adults followed over a five-year period (Bailly et al, 2018), response of hospice patients to the diagnosis of terminal illness by cultivating wisdom through a balance between active acceptance of the current situation and continued push for a galvanized growth (Montross-Thomas et al, 2018), and significant contributions of close friends and leisure activity engagement to better cognitive performance in old age (Ihle et al, 2018). There are accompanying commentaries (Baiyewu, 2018;Forlenza and Vallada, 2018;Pachana and Mitchell, 2018) from Nigeria, Brazil, and Australia, respectively, which discuss both limitations and implications of those studies.…”
Section: Positive Psychiatry Comes Of Agementioning
confidence: 99%
“…The majority of studies were conducted in North America (n=26),19–44 with 11 from Europe,45–55 7 from Oceania4 56–61 and 6 from Asia 62–67. Participants were sampled from hospice settings (inpatient and hospice at home) in 27 studies,4 19 25 26 28–35 38–40 45–47 53 54 56–58 60–62 66 acute and long-term care settings in 9,22 27 44 55 59 63–65 67 general practices settings in 3,42 48 52 cancer centres in 4,23 24 36 37 a mix of settings in 3 studies21 49 50 and palliative care centres in 2 studies 43 51. One study provided no details on where participants were recruited from 41.…”
Section: Resultsmentioning
confidence: 99%
“…For 10 datasets, studies were included where they reported that the majority of patients (ie, ≥50%) had died within a year or before study completion 23 24 26 27 31 34 36 39 46 59 61. Twenty-one datasets included participants with a mix of chronic conditions,19 21 25 28–33 39–45 47–50 53 54 56–58 61 18 datasets included only participants with cancer,4 20 23 24 26 27 34–37 46 51 52 59 60 62–67 and 1 dataset included participants with only neurodegenerative diseases 55. Two datasets did not specify participants’ conditions 22 38…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation